2005
DOI: 10.1007/s00192-005-1347-9
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of preoperative and intraoperative evaluation of patients undergoing pelvic reconstructive surgery for pelvic organ prolapse using the pelvic organ prolapse quantification system

Abstract: Intraoperative evaluation of the prolapse can reveal significant changes as compared with the preoperative situation. In general, the prolapse is more pronounced especially in the middle and posterior compartment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 11 publications
1
21
1
2
Order By: Relevance
“…Even though examiners were randomly allocated to reduce bias and maintain heterogeneity in the level of traction applied, they were not specifically blinded. This may have led to the larger difference between point C measured with traction pre-operatively and intra-operatively in our study, compared to 2.3 cm reported by Vierhout et al [7].…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Even though examiners were randomly allocated to reduce bias and maintain heterogeneity in the level of traction applied, they were not specifically blinded. This may have led to the larger difference between point C measured with traction pre-operatively and intra-operatively in our study, compared to 2.3 cm reported by Vierhout et al [7].…”
Section: Discussioncontrasting
confidence: 55%
“…patient position, vaginal specula, retractors or tractors, type of straining and fullness of bladder and rectum [5]. Furthermore, there is evidence to suggest that intra-operative examination of prolapse under anaesthesia could be significantly different from pre-operative examination even if the POP-Q system is used [6][7][8]. Increase in uterine descent intraoperatively may be due to the absence of levator coactivation under anaesthesia, progression of the prolapse or not eliciting the maximal uterine descent at the time of initial examination.…”
Section: Introductionmentioning
confidence: 99%
“…We found that performing a hysterectomy at the time of surgery significantly increased the success rate. Several authors have shown that prolapse assessed intra-operatively tends to be greater than pre-operative assessment [13,25], and in our study, 21% of women had no documentation of the degree of prolapse of the cuff or vagina. It would not be possible to perform a hysterectomy or vault procedure intraoperatively in the absence of consent, so inadequate preoperative assessment may partly account for the poor success rate in these women.…”
Section: Discussionmentioning
confidence: 58%
“…The premenopausal women were submitted to blood drawn between days 2 and 5 of the menstrual cycle (proliferative phase) [11]. All subjects in a 45°semiupright position with an empty bladder in a birthing chair were examined during maximum Valsalva maneuver for staging of POP according to the criteria of the International Continence Society [18,19]. All examinations were performed by a senior gynecologist.…”
Section: Study Participantsmentioning
confidence: 99%